PEMANFAATAN BUKU DIGITAL DALAM MENINGKATKAN MINAT BACA - Ruddamayanti, Ruddamayanti (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The purpose of this paper is to provide an explanation for using digital books to increase students’ reading interest. As the background of this writing because of the low interest in reading students in textbooks and other books that are still in the form of ordinar y books. Digital books are one of altenative for students to increase reading interest. Because it can not be denied, now students hold more handphone than their books. The nature of digital books is practical and easy to carry everywhere making it easy for students to read whenever and wherever they want. So that it is expected that the use of digital books in increasing students interest in reading will be more efektif and efficient.